The Political Legitimacy And Doctrinal Maturity Of The Fatimid State (Journal of Namibian Studies : History Politics Culture, 2024)
Political legitimacy in Islamic history has seen significant developments and has been characterized by diversity in terms of the means to achieve power and secure the allegiance of the subjects. Among these states is the Fatimid Caliphate, which was distinguished by a unique legitimacy associated with several factors including doctrinal, genealogical, and proselytizing elements. All these aspects contributed to some extent to the establishment of this state's legitimacy. However, during its reign, the state experienced specific breakthroughs that led to weaknesses and a lack of cohesion. Initially, from the year 297 Hijri until 358 Hijri, it was a phase of building and establishing the state and laying its initial foundations and preserving them. Later, especially after the transfer of the Fatimid Caliphate to Egypt, the state began to enforce legitimacy through preachers and religious institutions, actively working on developing political legitimacy based on the Shia doctrinal vision and disseminating it among the people. Nevertheless, in a subsequent phase, especially during the reign of Caliph Al-Mustansir Billah, the state suffered from divisions and instances of fragmentation and lukewarmness in practicing this legitimacy and convincing the populace of it, while maintaining the state's prestige through it amid economic and political crises that spread within it, making it impossible to restore affairs to their proper  state again after ministers intervened in appointing and deposing caliphs.